2009
DOI: 10.1002/jts.20453
|View full text |Cite
|
Sign up to set email alerts
|

Mutual influence of posttraumatic stress disorder symptoms and chronic pain among injured accident survivors: A longitudinal study

Abstract: The relationship between acute stress disorder (ASD), posttraumatic stress disorder symptoms (PTSD), and chronic pain was investigated in a longitudinal study of injured accident victims (N = 323, 64.7% men). Assessments took place 5 days (T1), 6 (T2) months, and 12 (T3) months postaccident. Relations between pain and posttraumatic stress symptoms were tested by structural equation modeling. Subjects diagnosed with full or subsyndromal PTSD at T2 and at T3 (14 and 19%) reported significantly higher pain intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
100
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(119 citation statements)
references
References 42 publications
15
100
2
Order By: Relevance
“…a minimum score on a screening instrument). For example, three studies (Bryant et al, 2012; deRoon-Cassini et al, 2010; Jenewein et al, 2009) had a minimum hospital admission length (24–48 hours), and three studies (Bonne et al, 2001; Shalev et al, 2012; van Zuiden et al, 2017) had a minimum threshold or criterion for initial symptoms. These criteria screened for more severely injured or more symptomatic patients to be included in the studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…a minimum score on a screening instrument). For example, three studies (Bryant et al, 2012; deRoon-Cassini et al, 2010; Jenewein et al, 2009) had a minimum hospital admission length (24–48 hours), and three studies (Bonne et al, 2001; Shalev et al, 2012; van Zuiden et al, 2017) had a minimum threshold or criterion for initial symptoms. These criteria screened for more severely injured or more symptomatic patients to be included in the studies.…”
Section: Resultsmentioning
confidence: 99%
“…The International Consortium to Predict PTSD (ICPP) is an effort sponsored by the US National Institute of Mental Health to create a consortium of principal investigators of published and unpublished longitudinal PTSD studies (Bonne et al, 2001; Bryant, Creamer, O’Donnell, Silove, & McFarlane, 2008; deRoon-Cassini, Mancini, Rusch, & Bonanno, 2010; Hepp et al, 2008; Irish et al, 2008; Jenewein, Wittmann, Moergeli, Creutzig, & Schnyder, 2009; Matsuoka et al, 2009a; Mouthaan et al, 2014; Shalev et al, 2012, 2000, 2008; van Zuiden et al, 2017), combine their individual- and item-level data towards carrying out a pooled secondary analysis, and synthesize information about the predictors of PTSD. The ICPP’s goal is to pool and harmonize extant data sets so as to inform PTSD pathogenesis and prediction across trauma types, severity, geography, and clinical circumstances.…”
Section: Introductionmentioning
confidence: 99%
“…Mediation models should be chosen through assumptions that are either invoked based on theory or fulfilled by design features [56]. In accordance with this, our mediation models were based on earlier longitudinal research, which has highlighted the long term impact of PTSD symptoms on pain intensity [14] and has identified mechanisms that mediate the effect of PTSD symptoms on pain intensity [15], and cross-sectional research, which has investigated mediators of the relationship between PTSD and chronic pain [18][19][20][21]. The mediation models were also strengthened by the current data, which showed that the trauma producing the current PTSD symptoms happened on average 3-5 years prior to the time that the measures of pain and psychological flexibility were administered.…”
Section: Data Analysesmentioning
confidence: 99%
“…Jenewein, Wittman et al (2009) administered measures of PTSD and pain intensity to 323 injured accident victims five days after hospital admission and again at 6-and 12-months later and tested the influence of pain on PTSD and vice versa. The model which best fit the data found that in the first six months after the trauma, pain intensity and PTSD symptoms were mutually maintaining, but in the second six months PTSD symptoms impacted significantly on pain intensity but not the reverse [14]. More recently, Andersen, Karstoft et al (2016) assessed 198 individuals for pain intensity and psychological distress within 3 weeks after whiplash injury and again 3-and 6-months later.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation